209k views
5 votes
Evaluate 5x2–3(x–2)+x for x=3

User Jericevans
by
4.5k points

2 Answers

3 votes

The solution of 5x^2–3(x–2)+x for x = 3 is 45

Solution:

In this question we have been given an equation and asked to solve for a particular value of ‘x’.

The given equation is:


5x^(2)-3(x-2)+x

We have been asked to solve it for x=3.

So, we need to substitute the value of x as 3 in the equation and then simplify it as follows:


\begin{array}{l}{=5\left(3^(2)\right)-3(3-2)+3} \\\\ {=5(9)-3(1)+3} \\\\ {=45-3+3=45}\end{array}

Therefore, on solving the equation for x = 3 we get 45

User Dov Miller
by
5.1k points
4 votes
10 (assuming you meant 5 TIMES 2
Evaluate 5x2–3(x–2)+x for x=3-example-1
User Andre Miras
by
4.5k points